The importance of lipids for neurodevelopment in low and middle income countries - Okai-Mensah, Pervy; Brkić, Diandra; Hauser, Jonas (Frontiers in Nutrition, 2025)
This review focuses on the effects of polyunsaturated fatty acids (FA) supplementation on neurodevelopmental outcomes in the first year of life in low- and middle-income countries (LMIC). Lipids are an essential part of early life diet; they provide crucial FAs for brain development and healthy growth. The high cost of relevant food sources providing specific FAs restricts their use and consumption in LMIC where more than 3 billion people cannot afford a healthy diet. This narrative review summarizes current knowledge extracted from 24 studies on the impact of specific FAs on neurodevelopment from birth to 12 years of age, with a particular focus on LMICs. We illustrate that most studies focus on effects of polyunsaturated FAs supplementation on neurodevelopmental outcomes in the first year of life. The strongest evidence in the literature is on supplementation during pregnancy with omega-3 fatty acids, in particular alpha-linolenic acid (ALA) and omega-6 fatty acids, in particular linoleic acid (LA), which show promising effects on infant neurodevelopmental outcomes in LMIC. These two essential fatty acids (EFAs) are key substrates necessary to synthesize the long-chain poly-unsaturated fatty acids (LC-PUFA) docosahexaenoic acid (DHA) and arachidonic acid (ARA), which have been reported to be important for neurodevelopment. For the postnatal supplementation we did not observe a clear consensus across studies, either due to mixed finding before 2 years of life or due to the low number of studies beyond 2 years of life. Differences across studies in the choice of FAs, dosage, treatment windows, age and type of neurodevelopment assessments likely contribute to the complexity of the results observed in the studies investigating postnatal supplementation. Finally, this review underlies the need for more research into FAs that support optimal development of children in LMICs and highlight the importance to find affordable solutions without compromising on quality.